Fabrication of chitosan collagen glycerine scaffold for oral wound treatment - Mohamed Halim, Muhammad Lutfi; Mohd Zayi, Nora Azirah; Mohamad, Mohd Yusof; Harun @ Ismail, Ahmad Fahmi; Rostam, Muhamad Ashraf (Faculty of Engineering, Universiti Putra Malaysia (UPM), 2024)
The current study aimed to fabricate and evaluate chitosan collagen glycerine (CCG) scaffold for suitability for usage for oral wound treatment. The scaffolds were developed in three different ratios of chitosan: collagen; 30:70, 50:50, and 70:30. Parameters tested were morphology, mechanical strength, and cytocompatibility. The morphology of the scaffold was evaluated using scanning electron microscopy imaging (SEM). The biostability of the scaffold was tested by measuring its degradation rate over four weeks of being immersed in phosphate-buffered saline (PBS). The cytocompatibility of the CCG scaffold is evaluated after 3 days of seeding HTERT TIGKs cells obtained from ATCC onto the scaffold via 2,5-diphenyl-2H-tetrazolum bromide (MTT) assay. The mean pore size of the scaffolds obtained through measurement using SEM for each ratio is 141.76 ± 27.03um (30:70), 166.76 ± 41.88um (50:50), and 174.43 ± 34.78um (70:30). The biostability test found the degradation rate was the highest in the first week (70-87.5% weight loss) but declined drastically and had insignificant weight loss over the three remaining weeks. In terms of cytocompatibility, the CCG scaffold (30:70) has the highest cell count followed by the other ratios respectively; 50:50, and 70:30. In conclusion, the CCG scaffold has the potential for oral wound treatment.